Half-sweep successive over relaxation iterative method to solve two-point fuzzy boundary value problems - Dahalan, A.A. (American Institute of Physics Inc., 2015)
This study deals with the application of numerical methods in solving the fuzzy boundary value problems (FBVPs) which is discretized to derive second order fuzzy finite difference approximation equation. Then this fuzzy approximation equation is used to generate the fuzzy linear system. In addition to that, the fuzzy linear system will be solved iteratively by using Gauss-Seidel (GS), Full-Sweep Successive Over-Relaxation (FSSOR) and Half-Sweep Successive Over Relaxation (HSSOR) iterative methods. Then several numerical experiments are conducted to illustrate the effectiveness of HSSOR iterative method compared with the GS and FSSOR methods. Â© 2015 AIP Publishing LLC.